Impact of Hypertension on Serum Creatinine, eGFR, Albumin and Albumin Creatinine Ratio on Kidney Function among the Employees of Sylhet MAG Osmani Medical College and Hospital - Chanda , Arun Kumar; Ghosh, Bipul Chandra; Hoq , Md Enamul; Rimi, Sadia Afrin; Paul , Tonusree; Bhattacharjee, Tanusree; Jui, Yeasmin (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Urinary albumin levels and hypertension are distinctly linked to a heightened risk of all-cause mortality. The impact of albuminuria on mortality, whether in the presence or absence of hypertension, remains unclear. The objective of this study was to investigate the influence of hypertension on the kidney function of employees at a referral hospital through analyzing the albumin and albumin creatinine ratio. Method: This cross-sectional observational study was done in the Department of Physiology in conjunction with the Department of Nephrology at Sylhet MAG Osmani Medical College, from July 2022 to June 2023. Ethical approval was obtained from the ethical committee of Sylhet MAG Osmani Medical College. The study population comprised all voluntarily participating volunteers employed at Sylhet MAG Osmani Medical College and Hospital, aged between 18 and 59 years. A comprehensive medical history was obtained, and a physical examination was conducted. Blood pressure, serum creatinine, estimated glomerular filtration rate (eGFR), urinary albumin, and the ratio of albumin to creatinine in the urine (ACR) were the variables that had been studied. A semi-structured questionnaire was employed for data collection. Results: Sixty-seven participants (33.5%) in the study were identified as having hypertension. Urinary albumin levels were significantly elevated, while eGFR values were dramatically reduced in hypertension patients (p<0.05). A significant relationship was detected between serum creatinine and urine ACR (p<0.05). Conclusion: It has been observed that hypertension can have an effect on renal function tests. J Com Med Col Teachers’ Asso Jan 2025; 29(1): 59-64